Agent and method for treating disorders associated with cytidine deaminase or deoxycytidine deaminase overexpression - Nyce, Jonathan W. (My University, 2000)
An agent of the chemical formula C.sub.7 N.sub.3 H.sub.8 O.sub.2 R.sup.1 R.sup.2 XX.sup.1, wherein X and X.sup.1 are each independently C or N but not simultaneously, R.sup.1 is lower alkyl, alkenyl or alkynyl, halogen or haloalkyl, and R.sup.2 is H, --N.sub.3 --OH, amino or halogen; or pharmaceutically acceptable salts thereof. A method of treating a disorder associated with the overexpression of cytidine deaminase or deoxycytidine deaminase comprises administering to a subject in need of the treatment a compound of the chemical formula ##STR1## wherein X and X.sub.1 are each independently C or N; R.sup.1 is lower alkyl, lower alkenyl, lower alkynyl, halogen, or haloalkyl; and R.sup.2 H, --N.sub.3, --OH, amino, or halogen; or a pharmaceutically acceptable salt thereof in an amount effective to treat the disorder. Pharmaceutical formulations useful in the method of the present invention are also disclosed.